House of secrets - Columbus, Chris (Columbus, Chris. House of secrets (Series), 2013)
Cordelia, Brendan, and Eleanor Walker, aged fifteen to eight, must rely on a mysterious book to face the Wind Witch and her father, the Storm King, who have kidnapped Dr. and Mrs. Walker and brought them to a strange world of magic.